(untitled) (Global Journal of Human-Social Science, 2019)
This article looks at the philosophical & discursive roots of the theoretical trinity of International Relations (IR). It identifies the outset of political realism at the beginning of the early modern period and goes through a structural analysis of Thomas Hobbes opus magnum Leviathan. The article displays that the liberal belief that is the foundation of the current human rights regime on the international stage stems from a reinterpretation of the Hobbesi an picture relying on scriptural authority, not on rational argument. Finally, it identifies the current emergence of constructivism as a revival of Rousseaue an thought. Ultimately, the present article raises the question if these different modes of knowledge production might be displaying different phases in political history rather than ultimate truths about the political world.